Modulation of Tetrachloroethylene-Associated Kidney Effects by Nonalcoholic Fatty Liver or Steatohepatitis in Male C57BL/6J Mice. (9th September 2018) - Cichocki, Joseph A; Luo, Yu-Syuan; Furuya, Shinji; Venkatratnam, Abhishek; Konganti, Kranti; Chiu, Weihsueh A; Threadgill, David W; Pogribny, Igor P; Rusyn, Ivan
Abstract: Accounting for genetic and other (eg, underlying disease states) factors that may lead to inter-individual variability in susceptibility to xenobiotic-induced injury is a challenge in human health assessments. A previous study demonstrated that nonalcoholic fatty liver disease (NAFLD), one of the common underlying disease states, enhances tetrachloroethylene (PERC)-associated hepatotoxicity in mice. Interestingly, NAFLD resulted in a decrease in metabolism of PERC to nephrotoxic glutathione conjugates; we therefore hypothesized that NAFLD would protect against PERC-associated nephrotoxicity. Male C57BL/6J mice were fed a low-fat (LFD), high-fat (31% fat, HFD), or high-fat methionine/choline/folate-deficient (31% fat, MCD) diets. After 8 weeks mice were administered either a single dose of PERC (300 mg/kg i.g.) and euthanized at 1–36 h post dose, or five daily doses of PERC (300 mg/kg/d i.g.) and euthanized 4 h after last dose. Relative to LFD-fed mice, HFD- or MCD-fed mice exhibited decreased PERC concentrations and increased trichloroacetate (TCA) in kidneys. S -(1, 2, 2-trichlorovinyl)glutathione (TCVG), S -(1, 2, 2-trichlorovinyl)-l -cysteine (TCVC), and N -acetyl- S -(1, 2, 2, -trichlorovinyl)-l -cysteine (NAcTCVC) were also significantly lower in kidney and urine of HFD- or MCD-fed mice compared with LFD-fed mice. Despite differences in levels of nephrotoxic PERC metabolites in kidney, LFD- and MCD-fed mice demonstrated similar degree of nephrotoxicity. However, HFD-fed mice were less sensitive to PERC-induced nephrotoxicity. Thus, whereas both MCD- and HFD-induced fatty liver reduced the delivered dose of nephrotoxic PERC metabolites to the kidney, only HFD was protective against PERC-induced nephrotoxicity, possibly due to greater toxicodynamic sensitivity induced by methyl and choline deficiency. These results therefore demonstrate that pre-existing disease conditions can lead to a complex interplay of toxicokinetic and toxicodynamic changes that modulate susceptibility to the toxicity of xenobiotics.